Classification and Mapping of Mangrove Biodiversity as a Bioindicator of Environmental Degradation - Johari, Harry Irawan (Jurnal Biologi Tropis, 2025)
Mangrove ecosystems function as buffers against coastal abrasion, blue-carbon sinks, and habitats for coastal biota; their structural condition can be read as a bioindicator of environmental degradation. This study portrays the condition of mangroves in Lembar, West Lombok by analyzing station-level summaries (Stations I–III) using a descriptive–comparative approach to the number (Σ) of units per stratum (trees–poles–seedlings), aggregate basal area (units following the summary sheet), and species composition. The data were processed directly from the worksheet (February 2025) without normalization to m²/ha or calculation of diversity indices due to the absence of plot area and per-individual data. The results show Station II had the highest counts of trees (91) and poles (49) with seedlings (26); Station I was slightly lower (trees 90; poles 46; seedlings 31); and Station III was the lowest (trees 25; poles 22; seedlings 14). The aggregate basal-area pattern per stratum is consistent and confirms the dominance of stand structure at Station II. The composition of five species is consistent across all stations Avicennia marina, Rhizophora stylosa, R. mucronata, R. apiculata, and Sonneratia alba indicating a functioning microhabitat gradient. The discussion interprets structural indicators (Σ and basal area) as simple bioindicators: Station II reflects a lower risk of degradation, Station I an intermediate risk, and Station III a higher risk. Stand structure and species composition are effective operational bioindicators for setting management priorities—Station III as a target for intervention (pressure reduction/rehabilitation), Station II to be maintained through protection and monitoring, and Station I to be managed adaptively; going forward, normalizing basal area to m²/ha, computing H′/J′, and measuring pressure parameters are needed to strengthen comparability.